2008
DOI: 10.1016/j.thromres.2007.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Thrombopoietin levels increased in patients with severe acute respiratory syndrome

Abstract: Hematological changes in patients with Severe Acute Respiratory Syndrome (SARS) are common and frequently include thrombocytopenia. Using a ELISA method, we found an increase in thrombopoietin (TPO) levels in the plasma of convalesced SARS patients (290+/-53 pg/ml) and active SARS patients (251+/-23 pg/ml) comparing to that from normal control patients (228+/-17 pg/ml). In addition, the plasma from active SARS patients had an inhibitory effect on CFU-MK formation, which could be neutralized by anti-TGF-beta an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 22 publications
2
35
0
2
Order By: Relevance
“…Yang et al [13] have reported the increased thrombopoietin and thrombocyte counts in the SARS disease. Also, Vlacha and collegues have reported that the thrombocytosis had occured in serious lower respiratory tract infections [14].…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al [13] have reported the increased thrombopoietin and thrombocyte counts in the SARS disease. Also, Vlacha and collegues have reported that the thrombocytosis had occured in serious lower respiratory tract infections [14].…”
Section: Discussionmentioning
confidence: 99%
“…Consumptive coagulopathy is a typical feature in SIC/ DIC; however, that type of coagulopathy is usually not seen in COVID-19 in its early phase. IL-1β and IL-6 are known to induce thrombocytosis and hyperfibrinogenemia, and sustained inflammation may stimulate the production of these factors [21]. In addition, inflammation and coagulation are localized within the lung in early stages but with disease progression, hypercoagulability becomes systemic and proceeds towards SIC/DIC.…”
Section: Sepsis-induced Coagulopathy (Sic) and Disseminated Intravascmentioning
confidence: 99%
“…[17] In severe acute respiratory syndrome induced by a novel coronavirus, TGFb inhibits the effect of high TPO on megakaryocytopoiesis. [18] Inflammatory mediator interleukin 6 (IL-6), however, increases TPO production both in vitro and in vivo. [14] Our finding of high TPO during acute PUUV infection is in line with a previous observation [9] and consistent with both low platelet count and high plasma IL-6 in acute PUUV infection .…”
Section: Discussionmentioning
confidence: 99%